IMPLEMENTASI KARAKTER DISIPLIN PADA ANAK USIA DINI GUNA MENGURANGI PERUNDUNGAN PADA ANAK - Dian Nastiti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Character education for early childhood is intended to instil good values as the basis for further personal development. Character education for early childhood is to build the nation’s mental and character for the future. Bullying is one of the negative behaviours that children could do as the impact of moral deterioration. Hence, it is necessary to instil character education in early childhood to reduce the number of bullying. This article reports a study about the strategy of building disciplined character for children in early childhood through programmed activities and exemplary in order to reduce bullying for children. The implementation of disciplined character with school programmed activities included in daily learning activities, for example, teachers implementing values like justice, respect, and honesty as part of daily learning either in or out of the classroom. In the implementation of disciplined character by exemplary, teachers and parents become role models in disciplined character habits for the children. The pattern of parents’ parenting style for children influenced the cultural relationship of parental discipline style. The parents' attitudes and behaviours toward children and the environment the students grew up are important for personality development.